ACTA1-related congenital myopathy in a neonate: a case report and literature review - Zhao, Lingxia; Deng, Feng; Cai, Baohuan (Frontiers in Pediatrics, 2026)
BackgroundACTA1-related congenital myopathies are rare neuromuscular disorders with significant genotypic heterogeneity, often causing severe neonatal multisystem involvement. This study presents a severe neonatal case with a pathogenic ACTA1 variant and reviews literature to highlight diagnostic and management challenges.Case presentationA female infant was born via cesarean section at 39+1 weeks to a non-consanguineous mother. Prenatal ultrasound showed polyhydramnios. She presented with severe birth asphyxia (Apgar 3 at 1 min, 5 at 5 min), requiring immediate resuscitation. Physical examination revealed profound hypotonia, absent spontaneous movements, respiratory insufficiency necessitating mechanical ventilation, expressionless facies, and bulbar dysfunction. Laboratory tests indicated metabolic acidosis and elevated lactate and creatine kinase. Electromyography (EMG) demonstrated reduced motor amplitudes and spontaneous fibrillations. Whole-exome sequencing identified a de novo heterozygous pathogenic variant in ACTA1 (c.227G>A, p. Gly76Asp), confirming ACTA1-related congenital myopathy. Care was withdrawn on day 18 due to poor neurologic recovery.ConclusionThis case highlights three critical implications: (1) the significant clinical overlap between ACTA1 myopathy and perinatal asphyxia, underscoring the necessity of genetic testing in hypotonic neonates with atypical presentations; (2) the grave prognosis of early-onset ACTA1 mutations, which mandates early palliative care consultation; and (3) the essential role of a precise genetic diagnosis in defining phenotypes and informing future targeted therapies, such as gene therapy.